Formowanie się chrześcijańskich obrzędów małżeńskich na podstawie Carmen XXV Paulina z Noli - Pałucki, Jerzy (Vox Patrum, 2016)
Church Fathers tried to combat the legacy of paganism and made tireless efforts towards Christianising family events, recalling the teaching of the Bible. Tertullian, for example, complained that the Christians of Carthage didn’t marry in the church. The article discusses Carmen XXV of Paulinus of Nola († 431), written for the occasion of marriage of Julian and Tysia. The poem contains one of the oldest descriptions of the ceremony of Christian marriage. Bishop of Nola pays attention to the spiritual dimension of the sacrament – specifically to its rich, full of symbols rite as well as to fact that the Christian meaning of the marriage ceremony should become the main focus for wedding preparations.